Helicobacter pylori infection: Host immune response, implications on gene expression and microRNAs - Targa Cadamuro, Aline Cristina [UNESP]; Teixeira Rossi, Ana Flavia [UNESP]; Maniezzo, Nathalia Maciel [UNESP]; Silva, Ana Elizabete [UNESP] (Baishideng Publ Grp Co Ltd, 2014)
Helicobacter pylori (H. pylori) infection is the most common bacterial infection worldwide. Persistent infection of the gastric mucosa leads to inflammatory processes and may remain silent for decades or progress causing more severe diseases, such as gastric adenocarcinoma. The clinical consequences of H. pylori infection are determined by multiple factors, including host genetic predisposition, gene regulation, environmental factors and heterogeneity of H. pylori virulence factors. After decades of studies of this successful relationship between pathogen and human host, various mechanisms have been elucidated. In this review, we have made an introduction on H. pylori infection and its virulence factors, and focused mainly on modulation of host immune response triggered by bacteria, changes in the pattern of gene expression in H. pylori-infected gastric mucosa, with activation of gene transcription involved in defense mechanisms, inflammatory and immunological response, cell proliferation and apoptosis. We also highlighted the role of bacteria eradication on gene expression levels. In addition, we addressed the recent involvement of different microRNAs in precancerous lesions, gastric cancer, and inflammatory processes induced by bacteria. New discoveries in this field may allow a better understanding of the role of major factors involved in the pathogenic mechanisms of H. pylori. (C) 2014 Baishideng Publishing Group Co., Limited. All rights reserved.
Keywords: Helicobacter pylori; Inflammation; Virulence factors; Immune response; Gastric lesions; Gastric cancer; Gene expression; MicroRNAs